Sex hormone levels in rural workers exposed to pesticides: A systematic review with meta-analysis - Jaciara Pinheiro de Souza; Cristiani Isabel Banderó Walker; Murilo de Jesus Porto; Jeferson de Menezes Souza; Liz Oliveira dos Santos; Maria de Fátima Santana de Souza Guerra; André Lacerda Braga Teles (Revista Contexto & Saúde)
The present study aims to analyze the excitatory and/or inhibitory effects of pesticide exposure on the production of male sex hormones in rural populations. The protocol for this systematic review was previously registered in PROSPERO (CRD42022354863) and follows the guidelines recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The research question addressed was: Does pesticides exposure cause excitatory and/or inhibitory effects on the production of sex hormones? The literature search was conducted from July 1 to July 17, 2023, in the following databases: Public Medline (PubMed), Latin American and Caribbean Literature in Health Sciences (LILACS), Science Direct, and Scientific Electronic Library (Scielo). The results indicate that pesticides exposure was associated with a significant decrease in testosterone levels (mean difference: -1.60, 95% CI: -2.47 to -0.72) and prolactin levels (mean difference: -1.28, 95 %: CI -2.19 to -0.37). In constrast, there was significant increase in Sex Hormone Binding Globulin (SHBG) levels (mean difference: 4.24, 95% CI: 1.54 to 6.93). No significant changes were observed in the levels of Follicle Stimulating Hormone (FSH) (mean difference: 0.98, 95% CI: 0.74 to 1.21) and Luteinizing Hormone (LH, mean difference: 0.44; 95% CI: 0.25 to 0.64) between the groups studied. In conclusion, evidence suggests that pesticide exposure may alter the production of various sex hormones. Specifically, individuals exposed to pesticides tend to exhibit lower levels of testosterone and prolactin, while SHBG levels are increased compared to those without exposure.